Answer:
Radius: ![r =\frac{\sqrt {21}}{6}](https://tex.z-dn.net/?f=r%20%3D%5Cfrac%7B%5Csqrt%20%7B21%7D%7D%7B6%7D)
![Center = (-\frac{3}{2}, -\frac{2}{3})](https://tex.z-dn.net/?f=Center%20%3D%20%28-%5Cfrac%7B3%7D%7B2%7D%2C%20-%5Cfrac%7B2%7D%7B3%7D%29)
Step-by-step explanation:
Given
![9x^2 + 9y^2 + 27x + 12y + 19 = 0](https://tex.z-dn.net/?f=9x%5E2%20%2B%209y%5E2%20%2B%2027x%20%2B%2012y%20%2B%2019%20%3D%200)
Solving (a): The radius of the circle
First, we express the equation as:
![(x - h)^2 + (y - k)^2 = r^2](https://tex.z-dn.net/?f=%28x%20-%20h%29%5E2%20%2B%20%28y%20-%20k%29%5E2%20%3D%20r%5E2)
Where
![r = radius](https://tex.z-dn.net/?f=r%20%3D%20radius)
![(h,k) =center](https://tex.z-dn.net/?f=%28h%2Ck%29%20%3Dcenter)
So, we have:
![9x^2 + 9y^2 + 27x + 12y + 19 = 0](https://tex.z-dn.net/?f=9x%5E2%20%2B%209y%5E2%20%2B%2027x%20%2B%2012y%20%2B%2019%20%3D%200)
Divide through by 9
![x^2 + y^2 + 3x + \frac{12}{9}y + \frac{19}{9} = 0](https://tex.z-dn.net/?f=x%5E2%20%2B%20y%5E2%20%2B%203x%20%2B%20%5Cfrac%7B12%7D%7B9%7Dy%20%2B%20%5Cfrac%7B19%7D%7B9%7D%20%3D%200)
Rewrite as:
![x^2 + 3x + y^2+ \frac{12}{9}y =- \frac{19}{9}](https://tex.z-dn.net/?f=x%5E2%20%20%2B%203x%20%2B%20y%5E2%2B%20%5Cfrac%7B12%7D%7B9%7Dy%20%3D-%20%5Cfrac%7B19%7D%7B9%7D)
Group the expression into 2
![[x^2 + 3x] + [y^2+ \frac{12}{9}y] =- \frac{19}{9}](https://tex.z-dn.net/?f=%5Bx%5E2%20%20%2B%203x%5D%20%2B%20%5By%5E2%2B%20%5Cfrac%7B12%7D%7B9%7Dy%5D%20%3D-%20%5Cfrac%7B19%7D%7B9%7D)
![[x^2 + 3x] + [y^2+ \frac{4}{3}y] =- \frac{19}{9}](https://tex.z-dn.net/?f=%5Bx%5E2%20%20%2B%203x%5D%20%2B%20%5By%5E2%2B%20%5Cfrac%7B4%7D%7B3%7Dy%5D%20%3D-%20%5Cfrac%7B19%7D%7B9%7D)
Next, we complete the square on each group.
For ![[x^2 + 3x]](https://tex.z-dn.net/?f=%5Bx%5E2%20%20%2B%203x%5D)
1: Divide the ![coefficient\ of\ x\ by\ 2](https://tex.z-dn.net/?f=coefficient%5C%20of%5C%20x%5C%20by%5C%202)
2: Take the ![square\ of\ the\ division](https://tex.z-dn.net/?f=square%5C%20of%5C%20the%5C%20division)
3: Add this ![square\ to\ both\ sides\ of\ the\ equation.](https://tex.z-dn.net/?f=square%5C%20to%5C%20both%5C%20sides%5C%20of%5C%20the%5C%20equation.)
So, we have:
![[x^2 + 3x] + [y^2+ \frac{4}{3}y] =- \frac{19}{9}](https://tex.z-dn.net/?f=%5Bx%5E2%20%20%2B%203x%5D%20%2B%20%5By%5E2%2B%20%5Cfrac%7B4%7D%7B3%7Dy%5D%20%3D-%20%5Cfrac%7B19%7D%7B9%7D)
![[x^2 + 3x + (\frac{3}{2})^2] + [y^2+ \frac{4}{3}y] =- \frac{19}{9}+ (\frac{3}{2})^2](https://tex.z-dn.net/?f=%5Bx%5E2%20%20%2B%203x%20%2B%20%28%5Cfrac%7B3%7D%7B2%7D%29%5E2%5D%20%2B%20%5By%5E2%2B%20%5Cfrac%7B4%7D%7B3%7Dy%5D%20%3D-%20%5Cfrac%7B19%7D%7B9%7D%2B%20%28%5Cfrac%7B3%7D%7B2%7D%29%5E2)
Factorize
![[x + \frac{3}{2}]^2+ [y^2+ \frac{4}{3}y] =- \frac{19}{9}+ (\frac{3}{2})^2](https://tex.z-dn.net/?f=%5Bx%20%2B%20%5Cfrac%7B3%7D%7B2%7D%5D%5E2%2B%20%5By%5E2%2B%20%5Cfrac%7B4%7D%7B3%7Dy%5D%20%3D-%20%5Cfrac%7B19%7D%7B9%7D%2B%20%28%5Cfrac%7B3%7D%7B2%7D%29%5E2)
Apply the same to y
![[x + \frac{3}{2}]^2+ [y^2+ \frac{4}{3}y +(\frac{4}{6})^2 ] =- \frac{19}{9}+ (\frac{3}{2})^2 +(\frac{4}{6})^2](https://tex.z-dn.net/?f=%5Bx%20%2B%20%5Cfrac%7B3%7D%7B2%7D%5D%5E2%2B%20%5By%5E2%2B%20%5Cfrac%7B4%7D%7B3%7Dy%20%2B%28%5Cfrac%7B4%7D%7B6%7D%29%5E2%20%5D%20%3D-%20%5Cfrac%7B19%7D%7B9%7D%2B%20%28%5Cfrac%7B3%7D%7B2%7D%29%5E2%20%2B%28%5Cfrac%7B4%7D%7B6%7D%29%5E2)
![[x + \frac{3}{2}]^2+ [y +\frac{4}{6}]^2 =- \frac{19}{9}+ (\frac{3}{2})^2 +(\frac{4}{6})^2](https://tex.z-dn.net/?f=%5Bx%20%2B%20%5Cfrac%7B3%7D%7B2%7D%5D%5E2%2B%20%5By%20%2B%5Cfrac%7B4%7D%7B6%7D%5D%5E2%20%3D-%20%5Cfrac%7B19%7D%7B9%7D%2B%20%28%5Cfrac%7B3%7D%7B2%7D%29%5E2%20%2B%28%5Cfrac%7B4%7D%7B6%7D%29%5E2)
![[x + \frac{3}{2}]^2+ [y +\frac{4}{6}]^2 =- \frac{19}{9}+ \frac{9}{4} +\frac{16}{36}](https://tex.z-dn.net/?f=%5Bx%20%2B%20%5Cfrac%7B3%7D%7B2%7D%5D%5E2%2B%20%5By%20%2B%5Cfrac%7B4%7D%7B6%7D%5D%5E2%20%3D-%20%5Cfrac%7B19%7D%7B9%7D%2B%20%5Cfrac%7B9%7D%7B4%7D%20%2B%5Cfrac%7B16%7D%7B36%7D)
Add the fractions
![[x + \frac{3}{2}]^2+ [y +\frac{4}{6}]^2 =\frac{-19 * 4 + 9 * 9 + 16 * 1}{36}](https://tex.z-dn.net/?f=%5Bx%20%2B%20%5Cfrac%7B3%7D%7B2%7D%5D%5E2%2B%20%5By%20%2B%5Cfrac%7B4%7D%7B6%7D%5D%5E2%20%3D%5Cfrac%7B-19%20%2A%204%20%2B%209%20%2A%209%20%2B%2016%20%2A%201%7D%7B36%7D)
![[x + \frac{3}{2}]^2+ [y +\frac{4}{6}]^2 =\frac{21}{36}](https://tex.z-dn.net/?f=%5Bx%20%2B%20%5Cfrac%7B3%7D%7B2%7D%5D%5E2%2B%20%5By%20%2B%5Cfrac%7B4%7D%7B6%7D%5D%5E2%20%3D%5Cfrac%7B21%7D%7B36%7D)
![[x + \frac{3}{2}]^2+ [y +\frac{4}{6}]^2 =\frac{7}{12}](https://tex.z-dn.net/?f=%5Bx%20%2B%20%5Cfrac%7B3%7D%7B2%7D%5D%5E2%2B%20%5By%20%2B%5Cfrac%7B4%7D%7B6%7D%5D%5E2%20%3D%5Cfrac%7B7%7D%7B12%7D)
![[x + \frac{3}{2}]^2+ [y +\frac{2}{3}]^2 =\frac{7}{12}](https://tex.z-dn.net/?f=%5Bx%20%2B%20%5Cfrac%7B3%7D%7B2%7D%5D%5E2%2B%20%5By%20%2B%5Cfrac%7B2%7D%7B3%7D%5D%5E2%20%3D%5Cfrac%7B7%7D%7B12%7D)
Recall that:
![(x - h)^2 + (y - k)^2 = r^2](https://tex.z-dn.net/?f=%28x%20-%20h%29%5E2%20%2B%20%28y%20-%20k%29%5E2%20%3D%20r%5E2)
By comparison:
![r^2 =\frac{7}{12}](https://tex.z-dn.net/?f=r%5E2%20%3D%5Cfrac%7B7%7D%7B12%7D)
Take square roots of both sides
![r =\sqrt{\frac{7}{12}}](https://tex.z-dn.net/?f=r%20%3D%5Csqrt%7B%5Cfrac%7B7%7D%7B12%7D%7D)
Split
![r =\frac{\sqrt 7}{\sqrt 12}](https://tex.z-dn.net/?f=r%20%3D%5Cfrac%7B%5Csqrt%207%7D%7B%5Csqrt%2012%7D)
Rationalize
![r =\frac{\sqrt 7*\sqrt 12}{\sqrt 12*\sqrt 12}](https://tex.z-dn.net/?f=r%20%3D%5Cfrac%7B%5Csqrt%207%2A%5Csqrt%2012%7D%7B%5Csqrt%2012%2A%5Csqrt%2012%7D)
![r =\frac{\sqrt {84}}{12}](https://tex.z-dn.net/?f=r%20%3D%5Cfrac%7B%5Csqrt%20%7B84%7D%7D%7B12%7D)
![r =\frac{\sqrt {4*21}}{12}](https://tex.z-dn.net/?f=r%20%3D%5Cfrac%7B%5Csqrt%20%7B4%2A21%7D%7D%7B12%7D)
![r =\frac{2\sqrt {21}}{12}](https://tex.z-dn.net/?f=r%20%3D%5Cfrac%7B2%5Csqrt%20%7B21%7D%7D%7B12%7D)
![r =\frac{\sqrt {21}}{6}](https://tex.z-dn.net/?f=r%20%3D%5Cfrac%7B%5Csqrt%20%7B21%7D%7D%7B6%7D)
Solving (b): The center
Recall that:
![(x - h)^2 + (y - k)^2 = r^2](https://tex.z-dn.net/?f=%28x%20-%20h%29%5E2%20%2B%20%28y%20-%20k%29%5E2%20%3D%20r%5E2)
Where
![r = radius](https://tex.z-dn.net/?f=r%20%3D%20radius)
![(h,k) =center](https://tex.z-dn.net/?f=%28h%2Ck%29%20%3Dcenter)
From:
![[x + \frac{3}{2}]^2+ [y +\frac{2}{3}]^2 =\frac{7}{12}](https://tex.z-dn.net/?f=%5Bx%20%2B%20%5Cfrac%7B3%7D%7B2%7D%5D%5E2%2B%20%5By%20%2B%5Cfrac%7B2%7D%7B3%7D%5D%5E2%20%3D%5Cfrac%7B7%7D%7B12%7D)
and ![-k = \frac{2}{3}](https://tex.z-dn.net/?f=-k%20%3D%20%5Cfrac%7B2%7D%7B3%7D)
Solve for h and k
and ![k = -\frac{2}{3}](https://tex.z-dn.net/?f=k%20%3D%20-%5Cfrac%7B2%7D%7B3%7D)
Hence, the center is:
![Center = (-\frac{3}{2}, -\frac{2}{3})](https://tex.z-dn.net/?f=Center%20%3D%20%28-%5Cfrac%7B3%7D%7B2%7D%2C%20-%5Cfrac%7B2%7D%7B3%7D%29)
Answer:
Mean for a binomial distribution = 374
Standard deviation for a binomial distribution = 12.97
Step-by-step explanation:
We are given a binomial distribution with 680 trials and a probability of success of 0.55.
The above situation can be represented through Binomial distribution;
![P(X=r) = \binom{n}{r}p^{r} (1-p)^{n-r} ; x = 0,1,2,3,.....](https://tex.z-dn.net/?f=P%28X%3Dr%29%20%3D%20%5Cbinom%7Bn%7D%7Br%7Dp%5E%7Br%7D%20%281-p%29%5E%7Bn-r%7D%20%3B%20x%20%3D%200%2C1%2C2%2C3%2C.....)
where, n = number of trials (samples) taken = 680 trials
r = number of success
p = probability of success which in our question is 0.55
So, it means X <em>~ </em>
<em><u>Now, we have to find the mean and standard deviation of the given binomial distribution.</u></em>
- Mean of Binomial Distribution is given by;
E(X) = n
p
So, E(X) = 680
0.55 = 374
- Standard deviation of Binomial Distribution is given by;
S.D.(X) =
=
=
= 12.97
Therefore, Mean and standard deviation for binomial distribution is 374 and 12.97 respectively.
Answer:
So the final answer is
![-8\sqrt{3}](https://tex.z-dn.net/?f=-8%5Csqrt%7B3%7D)
Step-by-step explanation:
Radicals:
In mathematics, a radical expression is defined as any expression containing a radical (√) symbol. Many people mistakenly call this a 'square root' symbol, and many times it is used to determine the square root of a number. However, it can also be used to describe a cube root, a fourth root, or higher.
The given expression is
![-5\sqrt{3} -3\sqrt{3}](https://tex.z-dn.net/?f=-5%5Csqrt%7B3%7D%20-3%5Csqrt%7B3%7D)
Now take common radical out so we will get
![\sqrt{3}(-5-3)](https://tex.z-dn.net/?f=%5Csqrt%7B3%7D%28-5-3%29)
Now add the Parenthesis part.
![\sqrt{3}(-8)](https://tex.z-dn.net/?f=%5Csqrt%7B3%7D%28-8%29)
So the final answer is
![-8\sqrt{3}](https://tex.z-dn.net/?f=-8%5Csqrt%7B3%7D)
Answer:
A reflection on the y axis, then a reflection on the x axis, then a translation of 7 units to the left
Step-by-step explanation:
plz mark me as brainliest